UJI AKTIVITAS PENGHAMBATAN POLIMERISASI HEME (1)-N-(2-NITROBENZIL)-1,10- FENANTROLINIUM IODIDA DAN (1)-N-(4-NITROBENZIL)-1,10- FENANTROLINIUM IODIDA SECARA IN VITRO - Nurani, Laela Hayu; Utami, Dwi; Widyaningsih, Wahyu; Narwanti, Iin; Nurwening, Eti; Jumina, Jumina (Universitas Ahmad Dahlan, 2014)
The inhibitory activity of heme polymerization of (1)-N-(2-nitrobenzyl)-1,10- phenantrolinium iodide and (1)-N-(4-nitrobenzyl)-1,10-phenantrolinium iodide have been done. This study aims to analyse the (1)-N-(2-nitrobenzyl)-1,10-phenantrolinium iodide and (1)-N-(4-nitrobenzyl)-1,10-phenantrolinium iodide as inhibitory of polimerization heme. Analysis of heme inhibtory polimerization activity used the experimental in vitro method. The activity showed by IC50 (the capable concentration of extract to inhibiting polymerization heme by 50% ). The IC50 value acquired by probit analysis. Assess IC50 of (1)-N-(2-nitrobenzyl)- 1,10-phenantrolinium iodide not to be identified, (1)-N-(4-nitrobenzyl)-1,10-phenantrolinium iodide and chloroquine by successively are 0,571Â±0,071; 25,498Â±1,876 mg/mL. The result showed the (1)-N-(4-nitrobenzyl)-1,10-phenantrolinium iodide had the highest value of the heme polymerization inhibitory activity than chloroquin, (1)-N-(2-nitrobenzyl)-1,10- phenantrolinium iodide hadnât the heme polymerization inhibitory activity.